The state and importance of discipline Descriptive geometry in geometric-graphic preparation of bachelors - Kelmagambetov N.K. , Келмағамбетов Н.К. (Рroblems of engineering and professional education, 2022)
The article presents a method for modeling a cross-section with a transverse surface, which is a geometric model of the regularity characterizing the properties of multicomponent building materials, and an algorithm for identifying an analytical model.